The impact of the OPEC announcement on the oil companies' share prices - Graicer, Rafael; Nery, Thiago Affonso; Jucá, Michele Nascimento; Hadad Junior, Eli; Bastos, Douglas Dias (Revista de Administração da UFSM, 2021)
Purpose: This study aims at verifying the negative impact of the announcement made by OPEC to maintain oil production - on March 5, 2020 - on the oil companies´ share prices in the main countries of Latin America and the BRIC´s. Design/methodology/approach: Such objective is verified through an event whose final sample consists of 29 oil companies of Brazil, Chile, Colombia, Russia, India and China. Findings: H1- OPEC announcement negatively affects the share price of oil companies- is not confirmed. However, H2 – OPEC announcement differently affects the share price of oil companies in Latin America and other emerging countries that make up the BRIC - is confirmed. Research limitations/implications: The sample considers only oil companies operating in the oil and integrated gas segments, as well as oil and gas exploration and production. Practical implications: These results expand the understanding of the impact of oil commodity price shocks on the share prices of oil companies in emerging countries, during the Covid-19 pandemic. Originality/value: Verification of a positive shock impact on the supply or the reduction in the oil price on the return on shares of BRIC´s companies and among other Latin American countries, during Covid-19.